2017
DOI: 10.1021/acs.jmedchem.6b01521
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Multitarget Agents Active as Broad-Spectrum Antivirals and Correctors of Cystic Fibrosis Transmembrane Conductance Regulator for Associated Pulmonary Diseases

Abstract: Enteroviruses (EVs) are among the most frequent infectious agents in humans worldwide and represent the leading cause of upper respiratory tract infections. No drugs for the treatment of EV infections are currently available. Recent studies have also linked EV infection with pulmonary exacerbations, especially in cystic fibrosis (CF) patients, and the importance of this link is probably underestimated. The aim of this work was to develop a new class of multitarget agents active both as broad-spectrum antiviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…Recently, we used a combined virtual docking/similarity clustering approach to identify, for the first time, single compounds acting as broad-spectrum antivirals and correctors of the F508del-CFTR folding defect. 22 We reasoned that the best way to kill two birds with one stone is if the birds are closed in the same cage: out of the metaphor, we focused on two targets (PI4KIIIβ and F508del-CFTR) that are localized within the endoplasmic reticulum (ER) to avoid additional problems of delivering the compound to different locations/compartments. On one side, our multi-target molecule will enter the ER and bind F508del-CFTR (like structurally related Corr-4a does) 27 to correct the folding defect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we used a combined virtual docking/similarity clustering approach to identify, for the first time, single compounds acting as broad-spectrum antivirals and correctors of the F508del-CFTR folding defect. 22 We reasoned that the best way to kill two birds with one stone is if the birds are closed in the same cage: out of the metaphor, we focused on two targets (PI4KIIIβ and F508del-CFTR) that are localized within the endoplasmic reticulum (ER) to avoid additional problems of delivering the compound to different locations/compartments. On one side, our multi-target molecule will enter the ER and bind F508del-CFTR (like structurally related Corr-4a does) 27 to correct the folding defect.…”
Section: Resultsmentioning
confidence: 99%
“…previously prepared, 22 with the 1-(2-hydroxyethyl)thiourea 7d gave the common intermediate 15, whose hydroxyl group was then protected as t-butyldiphenylsilyl (TBDPS) ether (Scheme 3). The free 2-amino group on the 4-methylthiazole ring (left part) was then properly acylated by reaction with different acyl chlorides or anhydrides to obtain compounds 17a-c after TBAFdeprotection of the crude mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides targeting IFN-associated pathways, other cellular targets may be used to develop synergistically acting therapeutics. We recently reported on a class of broad-spectrum enterovirus/RV inhibitors that are also correctors of the cystic fibrosis transmembrane conductance regulator (CFTR) folding 56 . Deficiencies in CFTR are associated with more than 90% of cystic fibrosis cases.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Partial inhibition of multiple targets with a single multi-target drug seems more effective than full inhibition of a single target, reducing on- and off-target-related toxicity and attrition rate in clinical development [ 17 ]. In line with this paradigm shift in antiviral drug discovery, our research group has successfully reported the development of multi-target antivirals active on multiple viruses and related diseases in vitro [ [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%